PENDEKATAN SAINTIFIK DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM - Munib, Abdul (Universitas Islam Madura, 2017)
The scientific approach is an innovative learning process designed specifically for students to actively construct the concept of knowledge through several processes or stages by observing to perform an identification of a problem, and from the results of the observation students are expected to be able to formulate the problem dilajutkan by formulating hypotheses, collect data with various techniques, and analyze data, and draw conclusions and communicate concepts, laws or principles that are